2021
DOI: 10.3390/nano11071639
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Sustainable Shape-Stabilized Phase Change Material for Thermal Energy Storage Based on Mg2+-Doped CaCO3/PEG Composites

Abstract: The properties of polyethylene glycol-6000 (PEG)/MgCaCO3, a low-cost shape-selective phase change material (ss-PCM), make it highly suitable for solar thermal applications. Nanosized porous MgO-doped CaCO3 with Mg molar concentrations of 5%, 10%, and 15% were synthesized using a hydrothermal technique. The prepared MgO-CaCO3 matrices were then impregnated with PEG to obtain PEG/MgCaCO3 as an ss-PCM. Samples identified as PEG-5MgCaCO3 (P-5-MCC), PEG-10MgCaCO3 (P-10-MCC), and PEG-15MgCaCO3 (P-15-MCC) were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Solar energy conversion into thermal energy and the energy storage capacity of PCMs may be computed simultaneously using the present technique, which takes into account the high latent heat and good optical characteristics of PCMs. 4 Also, PEG/Sc-SiO 2 absorbs higher light higher compared with pure PEG across the whole visible region. Several temperature recorders were placed under the solar simulators to evaluate the conversion of solar energy into thermal energy by PEG and PEG/Sc-SiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Solar energy conversion into thermal energy and the energy storage capacity of PCMs may be computed simultaneously using the present technique, which takes into account the high latent heat and good optical characteristics of PCMs. 4 Also, PEG/Sc-SiO 2 absorbs higher light higher compared with pure PEG across the whole visible region. Several temperature recorders were placed under the solar simulators to evaluate the conversion of solar energy into thermal energy by PEG and PEG/Sc-SiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that solar energy conversion efficiency (η) can be increased by incorporating organic PCMs in an inorganic support. 4 Although many materials selectively absorb visible light, collecting and converting full-band solar radiation are challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These options are more attractive when compared with other options because of the relatively high storage density and the fact that it is almost possible to achieve isothermal storage conditions. Proposed TES systems that use phase change materials (PCMs) [ 4 ] can store several times more energy than systems using sensitive storage materials, even when the same material types and volumes are used [ 5 ]. However, most phase change materials have the disadvantageous property of relatively low thermal conductivity [ 6 ], which strongly inhibits the energy charge and discharge rates.…”
Section: Introductionmentioning
confidence: 99%